La didattica delle passioni. Peculiarità e paradossi del tea- tro gesuita delle origini1 - Luana Salvarani (Firenze University Press, 2014)
The article considers the pedagogical function of the Jesuit theatre of the origins. Speaching about the "didactics of passions", the article catches the significant role of theatre to "show" and to "form" passions.